(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1871)
The author discusses the ecclesiastical and architectural history of the church of St Vigeans by observing the building itself and studying primary sources. In the second half of the paper he describes in detail the fragments of sculptured stones that were found in the church during a recent restoration.